2022
DOI: 10.3233/jad-220181
|View full text |Cite
|
Sign up to set email alerts
|

Does APOE ɛ4 Status Change How 24-Hour Time-Use Composition Is Associated with Cognitive Function? An Exploratory Analysis Among Middle-to-Older Adults

Abstract: Background: The 24 h time-use composition of physical activity, sedentary behavior, and sleep is linked to cognitive function in adults and may contribute to future dementia risk. However, the impact of reallocating time between behaviors may differ depending on an individual’s genetic dementia risk. Objective: To explore if there is an interaction between 24 h time-use composition and genetic dementia risk in relation to cognitive function, and to simulate how time-reallocations are associated with cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Few studies have examined 24-h day time use against cognitive function in older adults, and only one of these has used CoDA ( Dumuid et al, 2022 ). Our findings of no associations contradict the few previous studies that reported associations between time-use composition and cognitive function in healthy older adults ( Fanning et al, 2017 ; Wei et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have examined 24-h day time use against cognitive function in older adults, and only one of these has used CoDA ( Dumuid et al, 2022 ). Our findings of no associations contradict the few previous studies that reported associations between time-use composition and cognitive function in healthy older adults ( Fanning et al, 2017 ; Wei et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in participants who engage in lower levels of MVPA per day (i.e., 30 min/day), reallocating an additional 15 min of MVPA per day equates to a 50% increase in total MVPA, whereas for those with a baseline level of 90 min of MVPA per day, reallocating an additional 15 min is equivalent to a ∼16% increase only. Additionally, Dumuid et al (2022) recruited a sample from a wider age range (50–80 years), across a range of cardiovascular risk profiles (“low” and “elevated” cardiovascular disease risk), with a subsequently lower level of cognitive function (mean ACE-III score = 91). Taken together it is likely that the recruitment of a highly active, high-performing sample in the current study contributed to the largely null findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research and replication may be necessary to understand why mild physical activity may be more beneficial for cognitive resilience than vigorous physical activity in older APOE ɛ4 positive men. This finding may also be confounded by other variables associated with physically active time vs physically inactive time such as sedentary behaviour and/or sleep which have also been linked to cognition 24 . While we only have self-report data on physical activity in this dataset, recent advances in technology mean that it is possible to objectively measure daily activity and time use with through wearable devices which may help untangle these effects (e.g.…”
Section: Discussionmentioning
confidence: 99%